2007
DOI: 10.1371/journal.pone.0000806
|View full text |Cite
|
Sign up to set email alerts
|

Primary Role of Functional Ischemia, Quantitative Evidence for the Two-Hit Mechanism, and Phosphodiesterase-5 Inhibitor Therapy in Mouse Muscular Dystrophy

Abstract: BackgroundDuchenne Muscular Dystrophy (DMD) is characterized by increased muscle damage and an abnormal blood flow after muscle contraction: the state of functional ischemia. Until now, however, the cause-effect relationship between the pathogenesis of DMD and functional ischemia was unclear. We examined (i) whether functional ischemia is necessary to cause contraction-induced myofiber damage and (ii) whether functional ischemia alone is sufficient to induce the damage.Methodology/Principal Findings In vivo mi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
155
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 116 publications
(165 citation statements)
references
References 58 publications
7
155
0
Order By: Relevance
“…Two of these inhibitors, sildenafil and tadalafil, have been independently identified by others (20,26), thus validating our screening strategy as a way of finding pathways that might influence the skeletal muscle abnormalities in dystrophin-null fish. The other compounds identified in our screen target additional pathways and represent additional targets for therapy.…”
Section: Discussionsupporting
confidence: 56%
See 1 more Smart Citation
“…Two of these inhibitors, sildenafil and tadalafil, have been independently identified by others (20,26), thus validating our screening strategy as a way of finding pathways that might influence the skeletal muscle abnormalities in dystrophin-null fish. The other compounds identified in our screen target additional pathways and represent additional targets for therapy.…”
Section: Discussionsupporting
confidence: 56%
“…It has been shown that aminophylline has numerous antiinflammatory effects, including the inhibition of inflammatory mediators and activation of NF-κB (22)(23)(24)(25). Previously, other groups have reported that a PDE5 inhibitor restores mdx mouse muscle to normal (20,21,26). It is generally known that PDE inhibitors cause an increase in intracellular cAMP and/or cGMP.…”
Section: Discussionmentioning
confidence: 99%
“…From a therapeutic point of view, vascular dysfunction can be targeted with vasodilating drugs. Pharmacological augmentation of NO-cGMP signaling using phosphodiesterase 5 inhibitors to increase the blood supply to working mdx muscles can reduce post-exercise muscle damage and enhance nNOS-dependent mild exercise-induced inactivity in mdx mice (Asai et al 2007;Kobayashi et al 2008). Together, these data highlight the importance of the vasomodulatory function of sarcolemmal nNOSμ in promoting exercise performance in dystrophic muscle.…”
Section: Nnosμ Function In Neuromuscular Diseasementioning
confidence: 88%
“…The exercise intolerance shown by DMD patients appears to arise in part from vascular dysfunction, which has long been suspected to be a critical pathogenic mechanism in DMD (Asai et al 2007;Kobayashi et al 2008;Lai et al 2009;reviewed in Percival et al 2011). Sarcolemmal nNOSμ deficiency leads to unopposed α-adrenergic receptor-mediated vasoconstriction in the active hindlimbs of mice mdx and contracting forearms of DMD patients (Thomas et al 1998;Sander et al 2000).…”
Section: Nnosμ Function In Neuromuscular Diseasementioning
confidence: 99%
“…Sildenafil also significantly reduces exerciseinduced ischemia (33), a potentially important pathogenetic mechanism in dystrophin-deficient skeletal muscle (10,34). In fact, defects in cGMP signaling are also suggested from studies in dystrophin-deficient skeletal muscle (35,36), and recently, Asai et al (37) showed that treatment with tadalafil, another known PDE5 inhibitor, ameliorates contraction-induced skeletal muscle damage. Finally, sildenafil can cross the blood-brain barrier to inhibit brain PDE5A (38), which could theoretically affect sympathetic and parasympathetic outflow.…”
Section: Discussionmentioning
confidence: 99%